Sarawak state elections 2016 : revisiting federalism in Malaysia - Mohamed Nawab Mohamed Osman (2019)
The recent state elections in the Eastern Malaysian state of Sarawak in 2016 saw the ruling coalition, the Barisan Nasional, secure a comfortable victory through its component party, the Parti Pesaka Bumiputera Bersatu, led by the late Adenan Satem, who passed away suddenly on 11 January 2017. A key theme of Adenan's election campaign was greater autonomy for the state of Sarawak, while he also distanced himself from the troubles of the Najib Razak administration and the federal government. This paper seeks to examine the Sarawak state elections within the context of Malaysia's federalism. We argue that the state elections highlight how a lack of popularity and weakened federal government has allowed states to exercise more leverage in order to gain greater influence and autonomy, strengthening the original federal agreement of 1963 while inadvertently weakening the centre. We argue that Malaysia's claim to be a federation is largely superficial, as much power constitutionally rests with the federal government at the expense of state autonomy. This is demonstrated through both an examination of federalism as a broad concept and a brief history of centre–state relations in Malaysia. This paper posits that further “bargaining” by states with the federal government during election campaigns may be possible if the centre continues to exhibit political weakness.